Resveratrol Attenuates High-Fat Diet Induced Hepatic Lipid Homeostasis Disorder and Decreases m6A RNA Methylation - Wu, Jiamin; Li, Yi; Yu, Jiayao; Gan, Zhending; Wei, Wenyao; Wang, Chao; Zhang, Lili; Wang, Tian; Zhong, Xiang (Frontiers in Pharmacology, 2020)
Purpose: N6-methyladenosine (m6A) mRNA methylation is affected by dietary factors and associated with lipid metabolism, however, whether the regulatory role of resveratrol in lipid metabolism is involved in m6A mRNA methylation remain unknown. Here, the objective of this study was to investigate the effect of resveratrol on hepatic lipid metabolism and m6A RNA methylation in the liver of mice. Methods: A total of 24 male mice were randomly allocated to LFD (low-fat diet), LFDR (low-fat diet + resveratrol), HFD (high-fat diet), and HFDR (high-fat diet + resveratrol) groups for 12 weeks (n = 6/group). Final body weight of mice were measured before sacrificing. Perirhemtric fat, abdominal and epididymal fat, liver tissues, and serum were collected at sacrifice and analyzed. Briefly, mice phenotype, lipid metabolic index, and m6A modification in the liver were assessed. Results: Compared to the HFD group, dietary resveratrol supplementation reduced the body weight, relative abdominal, epididymal, and perirhemtric fat weight in high-fat-exposed mice, however, resveratrol significantly increased average daily feed intake in mice given high-fat diet. The amounts of serum low density lipoprotein cholesterol (LDL), liver total cholesterol (TC), triacylglycerol (TAG) were significantly decreased by resveratrol supplementation. In addition, Resveratrol significantly enhanced the levels of peroxisome proliferator-activated receptor alpha (PPARα), peroxisome proliferator-activated receptor beta/delta (PPARβ/δ), cytochrome P450 family 4 subfamily a polypeptide 10/14 (CYP4A10/14), acyl-CoA oxidase 1 (ACOX1), and fatty acid-binding protein 4 (FABP4) mRNA, and inhibited acyl-CoA carboxylase (ACC) mRNA levels in the liver. Furthermore, the resveratrol in high-fat diet increased the transcript levels of methyltransferase like 3 (METTL3), alkB homolog 5 (ALKBH5), fat mass and obesity associated protein (FTO), and YTH domain family 2 (YTHDF2), whereas decreased the level of YTH domain family 3 (YTHDF3) and m6A abundance in mice liver. Conclusion: The beneficial effect of resveratrol on lipid metabolism disorder under high-fat diet may be due to decrease of m6A RNA methylation and increase of PPARα mRNA, providing mechanistic insights into the function of resveratrol in alleviating the disturbance of lipid metabolism in mice.